Inhibition of renal interstitial fibrosis by mulberry leaf alkaloids in rats with diabetic nephropathy - Feng Wu; Li Wei (Linchuang shenzangbing zazhi)
ObjectiveTo explore whether or not mulberry leaf alkaloids can inhibit renal interstitial fibrosis in diabetic nephropathy （DN） rats.MethodsDN rat model was established by a high-fat diet and a tail vein injection of streptozotocin （STZ） in 50 Sprague-Dawley （SD） rats. The successfully modeled rats were randomly divided into five groups of model， benazepril and mulberry leaf alkaloid low/medium/high dose （n=10 each）. In control group， 10 rats received a standard diet and a tail vein injection of equal volume of sodium citrate buffer simultaneously. Benazepril group received 1.7 mg/kg benazepril， mulberry leaf alkaloid low/medium/high-dose groups 50/100/200 mg/kg mulberry leaf alkaloid and model and control groups 4 ml/kg normal saline once daily for 12 weeks. Urinary microalbumin （mAlb）， serum creatinine （Scr） and blood urea nitrogen （BUN） were measured by an automatic biochemical analyzer and endogenous creatinine clearance （Ccr） was calculated. Hematoxylin eosin （HE） staining was utilized for observing the pathological changes of renal tissue in each group； Masson staining for observing the deposition of collagen fibers in renal tissue and calculating the relative area of renal interstitial fibrosis. Reverse transcription-quantitative polymerase chain reaction （RT qPCR） was utilized for detecting the expressions of transforming growth factor β1 （TGF-β1）， connective tissue growth factor （CTGF）， Smad2， Smad3 and fibronectin （FN） messenger RNA （mRNA） in renal tissue of each group. TGF-β1， Smad2， Smad3， CTGF， FN protein expression and p-Smad2， p-Smad3 levels in renal tissue of each group was detected by Western blot.ResultsIn model group， glomerulus volume expanded， mesangial matrix proliferated， basement membrane thickened， renal tubular epithelial cells vacuolized and numerous inflammatory cells infiltrated in renal interstitium. Masson staining showed that a large number of blue gray collagen fibers were deposited. The pathological changes and fibrosis of vascular and renal tissues improved in varying degrees in mulberry leaf alkaloid low/medium/high-dose and benazepril groups. Compared with control group， mAlb， Scr， BUN， relative area of renal interstitial fibrosis and the expression of TGF-β1， CTGF， Smad2， Smad3， FN mRNA and protein and the levels of p-Smad2 and p-Smad3 spiked in all groups while Ccr declined （P<0.05）. Compared with model group， mAlb， Scr， BUN， relative area of renal interstitial fibrosis and the expressions of TGF-β1， Smad2， Smad3， CTGF， FN mRNA and protein and levels of p-Smad2 and p-Smad3 increased in mulberry leaf alkaloid low/medium/high-dose groups， benazepril group decreased， and Ccr increased （P<0.05）.ConclusionMulberry leaf alkaloids may reduce the levels of mAlb， Scr and BUN， up-regulate the level of Ccr， effectively inhibit renal interstitial fibrosis and delay the process of end-stage renal disease in DN rats.